Evaluasi Pengalaman Pengguna Pada Aplikasi Mobile Dengan Menggunakan UX Curve (Studi Kasus: BNI Mobile banking) - Vira Indriana; Hanifah Muslimah Az-Zahra; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mobile banking is a service that allows bank customers to conduct banking transactions through acellphone or a smartphone. One of the banks that provide mobile banking facilities is Bank NegaraIndonesia with BNI Mobile banking application. This research aims to evaluate long-term userexperience using the UX Curve Method which has 5 aspects to evaluate which are General UX,Attractiveness, Ease-of-Use, Utility and Degree of Usage. The data collected in this research is gatheredby giving 20 respondents a template curve. One hundred curves were gathered which were thencategorized into either Improving, Deteriorating or Stable based on how the curve was drawn. Afterbeing categorization, 50 curves as Improving, another 34 curves as Deteriorating, and another 16curves as Stable. Besides drawing curves, respondents were asked to give a reason which will be dividedinto positive and negative reasons. For the General UX aspect the average reason is 3,5, Attractivenessan average of 2,9, Ease-of-Use the average reason is 2,9, Utility average reason is 2,7, Degree of Usagethe average reason is 3,1.The reaction of respondents who expressed discomfort at experiencing certainerrors when using the BNI Mobile banking application is also recorded. A final questionnaire will thenbe distributed to identify the correlation between the curves and user satisfaction. The results from thefinal questionnaire were that all respondents agreed to recommend to BNI Mobile banking applicationto their friends.